2019
DOI: 10.1111/ap.12400
|View full text |Cite
|
Sign up to set email alerts
|

“It's very hard for me to say anything positive”: A qualitative investigation into borderline personality disorder treatment experiences in the Australian context

Abstract: Objective: To identify in the Australian context: (a) treatment and support services that are accessed by people living with borderline personality disorder (BPD) and their carers, (b) perceived benefits and challenges associated with these services, and (c) changes these individuals would like to see with regards to service provision and access. Method: This project involved semi-structured qualitative interviews with 12 participants (75% female, M age = 39.9, SD = 11.7), nine with lived experience of BPD, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…This is consistent with previous Australian research indicating that many GPs find it challenging to manage patients with difficult‐to‐treat depression in primary care and value the input of other professionals 26,27 . Further, substantial numbers of HPs indicated that they were likely to require assistance with ongoing management and referral of patients with mental disorders other than depression and anxiety, in line with research suggesting that the Australian health care system is challenged when meeting the needs of patients with personality disorders 28,29 or complex needs 12 …”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with previous Australian research indicating that many GPs find it challenging to manage patients with difficult‐to‐treat depression in primary care and value the input of other professionals 26,27 . Further, substantial numbers of HPs indicated that they were likely to require assistance with ongoing management and referral of patients with mental disorders other than depression and anxiety, in line with research suggesting that the Australian health care system is challenged when meeting the needs of patients with personality disorders 28,29 or complex needs 12 …”
Section: Discussionsupporting
confidence: 87%
“…The findings clearly show that consumers want to receive comprehensive, holistic and evidence‐based support, including psychotherapy (Carrotte et al., 2019 ). The data also highlight a shift in consumer preference from psychiatrists in 2011, to psychologists in 2017, as their main treating health professional.…”
Section: Discussionmentioning
confidence: 94%
“…A study by Zanarini and Frankenburg ( 2008 ) also demonstrated that individuals who are educated about BPD with up‐to‐date information immediately after diagnosis experience significantly lower short‐term impulsivity and interpersonal relationship distress. The recent SANE report (Carrotte et al., 2019 ) further highlights the problems with stigma from within health services, and the negative effects of unclear or insensitive communication from health professionals in the Australian setting.…”
Section: Introductionmentioning
confidence: 99%
“…BPD is highly stigmatized ( Cone, 2020 ; Kirtley et al, 2019 ; Masland and Null, 2021 ). Stigma can become internalized by individuals with BPD ( Grambal et al, 2016 ; Quenneville et al, 2020 ) and perceived BPD stigma can prevent people from accessing supports ( Carrotte et al, 2019 ). Morgan and Zimmerman et al (2015) suggest that reducing stigma may help improve assessment and diagnosis of BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Vlogging can provide an individual with peer support, enhance self-efficacy, reduce self-stigma and encourage recovery ( Sangeorzan et al, 2018 ). Comments to vlogs can give access to a wide variety of opinions and responses, however there is a lack of research into the comments to BPD-centred vlogs, about a disorder that is often stigmatized, underdiagnosed and misunderstood ( Carrotte et al, 2019 ; Dhaliwal et al, 2020 ; Zimmerman, 2015 ).…”
Section: Introductionmentioning
confidence: 99%